2011
DOI: 10.3892/or.2010.1088
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of CD147 gene expression via RNA interference reduces tumor cell invasion, tumorigenicity and increases chemosensitivity to cisplatin in laryngeal carcinoma Hep2 cells

Abstract: Abstract. CD147, also named extracelluar matrix metalloproteinase inducer (EMMPRIN), is a member of the immunoglobulin family and a glycoprotein enriched on the surface of tumor cells, which promotes invasion, metastasis, growth and survival of malignant cells, and is known to confer resistance to some chemotherapeutic drugs. To determine the possible role of CD147 in the invasive properties of laryngeal carcinoma, we used an RNA interference approach to silence CD147 expression in the Hep2 cell line at high l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…These results are in line with ours, suggesting that EMMPRIN might be relevant for the tumor proliferation and tumor growth of OSCC. Furthermore, knockdown of EMMPRIN in head and neck carcinomas decreased cellular proliferation and tumor growth in vitro and in vivo analyses [2830]. Mechanisms involved in tumor proliferation via EMMPRIN are poorly understood, but some authors have described the role of this receptor in association with cyclophilin A in the activation of ERK1/2 and p38 pathways [31].…”
Section: Discussionmentioning
confidence: 99%
“…These results are in line with ours, suggesting that EMMPRIN might be relevant for the tumor proliferation and tumor growth of OSCC. Furthermore, knockdown of EMMPRIN in head and neck carcinomas decreased cellular proliferation and tumor growth in vitro and in vivo analyses [2830]. Mechanisms involved in tumor proliferation via EMMPRIN are poorly understood, but some authors have described the role of this receptor in association with cyclophilin A in the activation of ERK1/2 and p38 pathways [31].…”
Section: Discussionmentioning
confidence: 99%
“…Membranous EMMPRIN expression, but not the overall EMMPRIN expression, was associated with poor response to cisplatin-based chemotherapies and a poor prognosis in advanced patients with non-small-cell lung carcinoma 48 . Silencing EMMPRIN increased the proliferation-inhibiting effect of cisplatin to lung cancer A549/DDP, 42 laryngeal carcinoma Hep2, 49 and gastric carcinoma SG7901 50 cells. However, we found no difference in EMMPRIN expression between ovarian carcinoma SKOV3 and SKOV3/DDP.…”
Section: Discussionmentioning
confidence: 94%
“…This was similar to the result of a study that used oral cancer cells ( 16 ). On the other hand, it was reported that CXCR4 was not involved in cell proliferation in HEp-2, an SCC of the larynx cell line ( 43 ). Therefore, these reports indicate that CXCR4 has different effects depending on the sub-location even within the same type of head and neck cancer and that detailed examination is necessary depending on the tumor site.…”
Section: Discussionmentioning
confidence: 99%